A Sensitive Homecage-Based Novel Object Recognition Task for Rodents - Wooden, Jessica I.; Spinetta, Michael J.; Nguyen, Teresa; O’Leary, Charles I.; Leasure, J. Leigh (Frontiers in Behavioral Neuroscience, 2021)
The recognition of novel objects is a common cognitive test for rodents, but current paradigms have limitations, such as low sensitivity, possible odor confounds and stress due to being performed outside of the homecage. We have developed a paradigm that takes place in the homecage and utilizes four stimuli per trial, to increase sensitivity. Odor confounds are eliminated because stimuli consist of inexpensive, machined wooden beads purchased in bulk, so each experimental animal has its own set of stimuli. This paradigm consists of three steps. In Step 1, the sampling phase, animals freely explore familiar objects (FO). Novel Objects (NO1 and NO2) are soiled with bedding from the homecage, to acquire odor cues identical to those of the FO. Steps 2 and 3 are test phases. Herein we report results of this paradigm from neurologically intact adult rats and mice of both sexes. Identical procedures were used for both species, except that the stimuli used for the mice were smaller. As expected in Step 2 (NO1 test phase), male and female rats and mice explored NO1 significantly more than FO. In Step 3 (NO2 test phase), rats of both sexes demonstrated a preference for NO2, while this was seen only in female mice. These results indicate robust novelty recognition during Steps 2 and 3 in rats. In mice, this was reliably seen only in Step 2, indicating that Step 3 was difficult for them under the given parameters. This paradigm provides flexibility in that length of the sampling phase, and the delay between test and sampling phases can be adjusted, to tailor task difficulty to the model being tested. In sum, this novel object recognition test is simple to perform, requires no expensive supplies or equipment, is conducted in the homecage (reducing stress), eliminates odor confounds, utilizes 4 stimuli to increase sensitivity, can be performed in both rats and mice, and is highly flexible, as sampling phase and the delay between steps can be adjusted to tailor task difficulty. Collectively, these results indicate that this paradigm can be used to quantify novel object recognition across sex and species.